DECODING CONTEXTUAL MEANINGS BASED ON LINGUISTIC AND DIDACTIC PRINCIPLES IN UZBEK-ENGLISH, ENGLISH-UZBEK DICTIONARIES - Eshquvatova , Mavjuda Sayfiddin qizi (Educational Research in Universal Sciences, 2023)
This article embarks on an exploration of the linguistic and didactic foundatios that underpin the interpretation of contextual meanings within Uzbek-English, English-Uzbek dictionaries. In addition, it delves into the intricate world of Uzbek-English, English-Uzbek dictionaries, unraveling the linguistic challenges and didactic factors essential for accurate interpretation of contextual meanings.